TANGGUNG JAWAB HUKUM PIDANA DAN PERDATA DOKTER DALAM KASUS MALPRAKTIK MEDIS: ANALISIS KOMPARATIF YURISPRUDENSI PENGADILAN DI INDONESIA - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
Cases of medical malpractice in Indonesia have shown a significant increase, with 51 complaints recorded between 2023 and 2025, creating a crisis of confidence in the healthcare sector and necessitating the resolution of disputes through both criminal and civil proceedings. This study aims to analyse the differences and similarities in court case law regarding medical malpractice cases, particularly in relation to the criminal and civil legal liability of doctors. The research method employed a literature review using a juridical-normative approach, analysing legislation such as Law No. 29 of 2004 on Medical Practice and Law No. 36 of 2009 on Health, as well as court rulings from District Courts up to the Supreme Court that constitute case law. The research findings indicate that criminal and civil liability differ fundamentally in terms of their objectives, standards of proof and the implications of a verdict, with civil proceedings having a higher success rate of 65–70 per cent compared to criminal proceedings at 40–45 per cent, due to a more lenient standard of proof. Key determining factors in both pathways include breaches of professional standards—which can be substantiated through expert opinions from the Indonesian Medical Commission—a strong causal link between the doctor’s actions and the patient’s harm, and the presence of an element of negligence on the part of the doctor. Civil compensation amounts to Rp2–5 billion for cases of permanent disability, whilst criminal sentences consist of 1–3 years’ imprisonment and the revocation of the doctor’s practising licence for 3–5 years. This study highlights the importance of comprehensive medical documentation, adherence to professional standards, and professional indemnity insurance to protect doctors from the risk of legal liability.